The Effect of Melatonin on Body Weight and the Potential use of Melatonin as an Anti-Obesity Agent - Gitti, Sama Atta; Khalaf , Rayan Zaidan; Alrubaie , Abdulhadi (AL-Kindy College Medical Journal, 2023)
Background: obesity is a major global health problem with more than 200 million obese men and almost 300 million obese women. Melatonin is a well-known molecule for its involvement in circadian rhythm regulation and has multiple pathological actions including control of appetite, sleep wake cycle and metabolic syndrome.Aim: to estimate the effect of melatonin supplements on obese patients on a calorie restricted diet in comparison to patients on lifestyle measures only in the form of weight loss, waist circumference and sleep quality.Subjects and Method: one hundred patients with body mass index > 24 were collected, fifty patients were started on melatonin 5 mg with calorie restricted diet and they were compared to fifty patients who were kept on lifestyle measures. After twelve weeks, patients were re-assessed for weight, waist circumference and sleep duration and quality and the development of any side effects. Data analyzed using paired t test.Results: patients’ group who were treated with melatonin has shown significant reduction in body weight (91.58. Vs 92.88, p value